Handbook of infection and alzheimer's disease - Miklossy, Judith (Advances in Alzheimer's disease (Series), 2017)
This handbook assembles and connects findings with regard to the infectious origin of Alzheimer's disease, and the data presented in its chapters deserves the attention of the neuroscience community, physicians and the health departments of governments worldwide by virtue of its amount and quality. This handbook offers a comprehensive overview of the current knowledge regarding the topic of infection and Alzheimer's disease, which could pinpoint the cause of this disease. Influential diagnosis, treatment and prevention strategies may also emerge from this crucial research area.